Efecto de número de podas en el cultivo de Piñón (Jatropha Curcas l.), en el distrito de Juan Guerra- San Martín - Pezo Valles, Abel (2009)
White Pinion (Jatropha curcas L.) is a shrub belonging to the Euphorbiaceae family. Native to Central America and Mexico but today is found throughout the tropical and subtropical zone. Can live 30-50 years and withstand periods of prolonged drought. Plants and seeds are inedible because curcin and diterpenas containing these alkaloids are albumins and toxic to humans and animals. That is why in the San Martin region is used as a fence to protect homes and farms in the countryside. In the San Martin region has started 2007 Pinion project at the research and promotion of the culture, as part of the Regional Biofuels Program "PROBIOSAM" with support from the Regional Agricultural Directorate St. Martin in strategic partnerships with public institutions as INIA, SENASA and private as GTZ, Group Tello, SNV (Netherlands); carrying out actions aimed at finding technological alternatives for clean energy crops that do not affect the environment, including the cultivation Pinion. In this context, the present research seeks to find exactly optimal agronomic responses by pruning and thus contribute to the productive devel